The United States Army food safety, security, and protection system - Nkwantabisa, Godfrey K. (Kansas State University, 2008)
In the military, documenting the occurrence of foodborne illnesses is a challenge. During peacetime only about ten percent of all foodborne illnesses are reported or properly diagnosed. Between 1998 and 1999, the Army had documented over 800 cases involving food or waterborne diseases. Service members are classified as highly susceptible when they are deployed or participating in extended field training exercises. Physical and emotional stress weakens the immune system, as does fatigue. These situations can be further aggravated by soldiers taking medications and/or exposed to exotic diseases or extreme environmental conditions. Thus it is very important for the United States Army to have a very good food safety, security, and protection system in place to maintain a readily deployable force. The United States Army monitors food safety, security, and defense through an extensive network of multiple organizations within and outside the army by researching from the fields of microbiology, sociology, economics, bioterrorism, etc. This network monitors food procured by the army from the source to the consumer and maintains accountability throughout the process. This report takes a look at the multiple organizations and the various strategies entailed in implementing food safety, security, and protection within the army and the entire Department of Defense. It emphasizes on some of the strategies that can be developed and applied in civilian establishments to improve the efficiency of the establishments. Such strategies include the implementation of the Prime Vendor System and the World Wide Web directory of sanitary approved sources which help to improve the ability to monitor the food with fewer personnel and also improve security and defense through solicitations and contracts. These strategies have been so effective that they are being used not only for food but for general logistics.
Keywords: Prime vendor; Approved sources; Food safety; Food security; Food defense; Agriculture, Food Science and Technology (0359); Health Sciences, Public Health (0573)